Influence of waste type with co-digestion system on methane production of patch digester stirred with exhaust gases - Mostafa Ashmawy; Osayed Abu-Elyazeed; Youssef Ahmed Attai; Mina Danial (Journal of Degraded and Mining Lands Management, 2022)
Investing in biogas is a viable option for the production of renewable energy. Production of renewable energy such as biogas has an impact on improving the environmental function and health impacts for all beneficiaries such as humans, lands, and ecosystems. As well recycling of solid waste could be considered waste management for economic development and protection of degraded and polluted lands. Anaerobic co-digestion has been practically applied in sewage sludge processing, agricultural and waste treatment and is recognized as an economical eﬀective way for waste reuse, treatment, and disposal. This paper presents three co-digestion experimental batches for thickened sludge with food waste, rice straw and cow waste. The mixtures were digested for thirty days, with 15 minutes of daily stirring using laboratory generator exhaust. A steel fixed dome anaerobic digester was used for experimental batches. The produced methane was recorded to be 65 %, 45.9 %, and 55 % when using thickened sludge with food waste, rice straw and cow waste, respectively. Cumulative methane was investigated for 7, 15 and 30 days to show the effect of time in methane production. The results showed that approximately 80 % of the produced methane was produced between 15 and 21 days. Anaerobic co-digestion increases the pH value of the three mixtures. The pH value was increased during anaerobic co-digestion due to the mineralization of the organic matter. However, pH values stayed between 6.0 and 8.0, which is better for growing and activating the methanogenic microorganisms as a reason for methane formation.